2020
DOI: 10.1155/2020/5163493
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Extended-Spectrum β-Lactamases in E. coli of Rats in the Region North East of Gabon

Abstract: Antibiotic resistance occurs in the environment by multiplication and the spread of multidrug-resistant bacteria that would be due to an improper and incorrect use of antibiotics in human and veterinary medicine. The aim of this study was to establish the prevalence of E.coli producing Extended-Spectrum beta-Lactamase (ESBL) antibiotics from rats and gregarious animals in a semirural area of Gabon and to evaluate the origin of a resistance distribution in the environment from animal feces. The bacterial cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
1
2
2
Order By: Relevance
“…However, antimicrobial resistance was obtained for aminoglycosides, tetracycline, nitrofurantoin, sulfamethoxazole-trimethoprim and phenicol in our study. Similar results have been observed in studies of terrestrial mammals in protected [ 45 ] and unprotected [ 45 , 57 ] areas of Gabon. E. coli is naturally sensitive to these antimicrobials [ 16 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, antimicrobial resistance was obtained for aminoglycosides, tetracycline, nitrofurantoin, sulfamethoxazole-trimethoprim and phenicol in our study. Similar results have been observed in studies of terrestrial mammals in protected [ 45 ] and unprotected [ 45 , 57 ] areas of Gabon. E. coli is naturally sensitive to these antimicrobials [ 16 ].…”
Section: Discussionsupporting
confidence: 90%
“…This study is the first identification of MDR E. coli (DECs) isolates assigned to different phylogenetic groups in a wild gorilla population in the PNMD in Gabon. Indeed, previous studies in Gabon have reported the prevalence of antimicrobial resistance in Enterobacteriaceae , including E. coli , isolated from the faeces of unprotected wild mammals from peri-urban areas [ 45 , 57 ], and the faeces of wild mammals from protected areas such as those in the PNMD [ 43 , 44 ] and the Lopé National Park [ 46 ]. In addition, studies conducted in the Lopé National Park have characterized E. coli isolates belonging to phylogenetic groups A, B1, B2 and D [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of 89% of E. coli found in the trapped rodents and shrews in our study is slightly higher than the 83.8% reported for rodents at the local zoo in Trinidad and Tobago [39] and 19.88% in rats in the east region of Gabon in Central Africa [40], Vancouver, Canada (41.5%), Berlin, Germany (58.2%), and Nairobi, Kenya (66.7%), [3,36,41,42]. In contrast, Nhung et al,2015 [43] reported an incidence of 90.91% of E. coli isolates from synanthropic rats and shrews in Vietnam.…”
Section: Discussioncontrasting
confidence: 76%
“…The prevalence of 89% of E. coli found in the trapped rodents and shrews in our study is slightly higher than the 83.8% reported for rodents at the local zoo in Trinidad and Tobago [ 41 ] and 19.88% in rats in the east region of Gabon in Central Africa [ 42 ], Vancouver, Canada (41.5%), Berlin, Germany (58.2%), and Nairobi, Kenya (66.7%), [ 36 ] [ 3 , 43 , 44 ]. In contrast, Nhung et al , 2015 [ 45 ] reported an incidence of 90.91% of E. coli isolates from synanthropic rats and shrews in Vietnam.…”
Section: Discussioncontrasting
confidence: 66%
“…Ho et al, 2015 [ 48 ] reported a prevalence of 7.7% and 13.9% of bla CTX-M producing multidrug-resistant E. coli in black and brown rats trapped in 18 districts of Hong Kong. Onanga et al , 2020 [ 42 ] reported human-origin E. coli carrying bla CTX-M genes in rats in Gabon, Central Africa.…”
Section: Discussionmentioning
confidence: 99%